Carcinoma in chronic calcific pancreatitis: review of literature - Naganath Babu, O. L.; Amarjothi, J. M. V.; Ramasamy, Villalan; Jesudason, Jeyasudhahar (International Surgery Journal, 2019)
Carcinoma occurring the setting of chronic calcific pancreatitis (CCP) are usually multifocal, poorly differentiated, advanced on presentation and associated with poor overall survival. Hence it is imperative that these patients should be identified in the early stages of malignant progression where by curative resection can then be employed. If not, only palliative approaches are feasible in advanced stages. We wish to present our experience of pancreatic carcinoma in the setting of CCP along with a review of literature.